uitwerking oefeningen kettingregel

$
\eqalign{
  & h(x) = \sqrt {x^2  - 4x}   \cr
  & h'(x) = \frac{1}
{{2\sqrt {x^2  - 4x} }} \cdot \left( {2x - 4} \right)  \cr
  & h'(x) = \frac{{2x - 4}}
{{2\sqrt {x^2  - 4x} }}  \cr
  & h'(x) = \frac{{x - 2}}
{{\sqrt {x^2  - 4x} }} \cr}
$


$
\eqalign{
  & h(x) = \left( {1 - x^{10} } \right)^{10}   \cr
  & h'(x) = 10\left( {1 - x^{10} } \right)^9  \cdot  - 10x^9   \cr
  & h'(x) =  - 100x^9 \left( {1 - x^{10} } \right)^9  \cr}
$


$
\eqalign{
  & h(x) = \sqrt {x^3  - 2x^2  + 2x - 1}   \cr
  & h(x) = \frac{1}
{{2\sqrt {x^3  - 2x^2  + 2x - 1} }} \cdot \left( {3x^2  - 4x + 2} \right)  \cr
  & h(x) = \frac{{3x^2  - 4x + 2}}
{{2\sqrt {x^3  - 2x^2  + 2x - 1} }} \cr}
$

©2004-2020 W.v.Ravenstein